Rheological properties of toasted bread using a modified American Association of Cereal Chemists method to determine compressive force values. Issue 6 (3rd October 2019) - Sato, Yukinori
Abstract: Background and objectives: Using a modified American Association of Cereal Chemists parameter for white bread crumb, CFV20, toasted bread firmness was investigated according to color changes on the surface of toasted bread. Findings: The L * value decreased significantly with toasting level, compared with changes in both a * and b * . To characterize the relationship between color and the rheological properties of the bread surface, a rheological parameter for bread surface was proposed, S in, which represents the slope of the force plotted against the plunger distance at a depth of <1 mm below the surface of the bread. The S in value of the toasted bread corresponded well with toasting level and CFV20 when toasted at low levels, suggesting that the surface firmness reflects the inner firmness of the toasted bread. A tactility sensory evaluation also supported the change in the CFV20 of toasted bread. In addition, the sensory evaluation values did not seem to be intimately influenced by the panel number, at least between n  = 5 and n  = 12. The rheological property CFV20 increased with decreasing L * . Therefore, L * seems to be a simple tool for measuring the rheological properties of the inner toasted bread. Conclusions: Color determination using the L * value of the toasted bread surface can be used to estimate the inner firmness of the bread. Significance and novelty: The texture of toasted bread has not been reported. The parameter S in was proposed as a rheological parameter representing the surface of toasted bread. The firmness of toasted bread according to the change in surface color was investigated in this study.